A Review of Soil Erosion Models with Special Reference to the needs of Humid Tropical Mountainous Environments - Avwunudiogba, Augustine; Franklin Hudson, Paul (European Journal of Sustainable Development, 2014)
Humid tropical mountainous environments (HTMEs) are generally considered sensitive ecological regions because anthropogenic disturbance often accelerate hillslope processes such as runoff, erosion, and sediment flux. Reducing accelerated erosion is necessary for the maintenance of the integrity, stability and sustainability of HTMEs. Soil erosion models (SOMs) are potential tools for predicting soil erosion, sediment flux, and the design and assessment of effectiveness of conservation management practices in HTMEs. Within this context, this study provides a critical review of the available SOMs with a focus on their applicability in HTMEs. The review indicates that because most SOMs have been developed for “flat agricultural lands” in temperate regions, to be useful in conservation planning in HTMEs models should be calibrated for local conditions. For humid tropical mountainous regions, lumped parameter models (LPMs) linked to Geographical Information Systems (GIS) are more practicable for conservation planning than sophisticated distributed parameter models (DPMs). This is due to the less stringent data requirements and ease to which land managers can implement LPMs, an essential consideration within the physical and socioeconomic context of HTMEs. Keywords:Soil erosion models; Humid tropics, Mountainous environments; Conservation planning